Collaboration Area For Environmental Management Related To Waste Management Around Pusur River Klaten - Mukti Ali; Alita Amamil Hana; Reza Ahmadiansah (IAIN Salatiga, 2021)
The objectives of this research were: to find out the role of Pusur Institute in processing waste as a form of environmental management, and the impact of waste management on ecological preservation in Pusur River Klaten. This research used descriptive qualitative. The results of the study indicated that the pusur river in Klaten can reduce waste by converting it into use value. Pusur Institute's waste processing activities included sorting waste according to its characteristics, recycling waste into crafts, recycling waste into fertilizer, and minimizing the use of items that produce waste. The impact of the waste processing at Pusur Institute Klaten was: (1) improving environmental quality, (2) improving health quality, (3) developing environmental knowledge.